Primary Breathing Survey Emergency with Oxygen Need Optimization and Nurse Caring on Covid-19 Patients in IGD UKI RSU Jakarta: Case Study - Aprilia Susanti; Erita Erita (Universitas Muhammadiyah Tangerang, 2022)
Emergency in Covid-19 is a respiratory tract infection caused by a new type of coronavirus (SARS-CoV-2) so that it can cause a decrease in oxygen levels in patients with saturation <95% Objective: To carry out emergency nursing care for19 patients Covid-. 19 with the measures in Primary Survey and Secondary Survey order to increase oxygen saturation >95%, reduce shortness of breath, regular breathing rhythm with a frequency of 20x/minute, symmetrical chest movements, and no chest muscle retraction Methods: The method of case study results uses a descriptive approach with a process approach. nursing care, independent action by monitoring the frequency of breath and oxygen saturation as well as giving the semi-fowler position, collaborative action by giving high concentration oxygen Non-Rebreathing Mask 10 liters/minute. Results: The patient's shortness of breath has been reduced with oxygen saturation increasing 99%, chest movement is symmetrical, irregular breathing rhythm 24x/minute is still partially resolved and the patient does not appear restless after being given high concentrations of oxygen. Conclusion: It takes speed and attitude caring towards patients to overcome anxiety and empathy, especially being a good listener by always providing support so that patients are always motivated to recover and providing independent action and the right collaboration of health workers so that the handling of Covid-19 can be resolved